2019
DOI: 10.3390/ijms21010036
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation in Etiology of Type 1 Diabetes Mellitus

Abstract: Type 1 diabetes mellitus (T1DM) is caused by an autoimmune destruction of the pancreatic β-cells, a process in which autoreactive T cells play a pivotal role, and it is characterized by islet autoantibodies. Consequent hyperglycemia is requiring lifelong insulin replacement therapy. T1DM is caused by the interaction of multiple environmental and genetic factors. The integrations of environments and genes occur via epigenetic regulations of the genome, which allow adaptation of organism to changing life conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 62 publications
(70 reference statements)
0
37
0
2
Order By: Relevance
“…Also, the same study showed a decrease in the level of the hypermethylated FOXP3 promoter in CD4+ T cells of LADA patients compared with controls; a biomarker of T1D (37). On the other hand, many studies showed variation of DNA methylation within the insulin region (INS), which represent the second most important locus associated with T1D (38)(39)(40)(41)(42). In fact, the variation of the DNA methylation within the INS gene is suspected to regulate INS gene transcription in the pancreatic β-cells as well as the medullary thymic epithelial cells.…”
Section: Epigenetics In T1dmentioning
confidence: 89%
“…Also, the same study showed a decrease in the level of the hypermethylated FOXP3 promoter in CD4+ T cells of LADA patients compared with controls; a biomarker of T1D (37). On the other hand, many studies showed variation of DNA methylation within the insulin region (INS), which represent the second most important locus associated with T1D (38)(39)(40)(41)(42). In fact, the variation of the DNA methylation within the INS gene is suspected to regulate INS gene transcription in the pancreatic β-cells as well as the medullary thymic epithelial cells.…”
Section: Epigenetics In T1dmentioning
confidence: 89%
“…Up to 50% of genetic risk for T1DM is due to the presence of susceptibility loci within the human leukocyte antigen (HLA) regions ( 5 7 ), with a strong linkage between T1DM and genetic variations of the HLA region on the short arm of chromosome 6 (6p21) ( 4 6 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a substantial increase in T1D incidence was observed [ 10 ], suggesting that multiple contributing factors must be involved in this higher incidence. Those factors include genetic and epigenetics contributors, autoimmunity, viral infections, antibiotics-mediated dysbiosis, gut microbiome composition, and lifestyle factors such as nutrition and modern diet [ 2 , 11 , 12 , 13 , 14 , 15 ]. Although certain HLA risk alleles are known to increase the susceptibility to T1D in children at risk, only 5% or fewer of them actually develop T1D [ 16 ], highlighting the importance of the non-genetic modifiers, in addition to other environmental factors in T1D pathogenesis [ 12 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%